Advanced Agriculture system - Shrinivas R. Zanwar; R. D. Kokate (Institute of Advanced Engineering and Science, 2012)
This article addresses the advanced system which improves agriculture processes like cultivation on ploughed land, based on robotic platform. We have developed a robotic vehicle having four wheels and steered by DC motor. The advanced autonomous system architecture gives us the opportunity to develop a complete new range of agricultural equipment based on small smart machines. The machine will cultivate the farm by considering particular rows and specific column at fixed distance depending on crop. The obstacle detection problem will also be considered, sensed by infrared sensor. The whole algorithm, calculation, processing, monitoring are designed with motors & sensor interfaced with microcontroller. The result obtained through example activation unit is also presented. The dc motor simulation with feedforward and feedback technique shows precise output. With the help of two examples, a DC motor and a magnetic levitation system, the use of MATLAB and Simulink for modeling, analysis and control is designed.DOI: http://dx.doi.org/10.11591/ijra.v1i2.382